Central African Republic : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion, Modification of Performance Criteria, Augmentation of Access, Extension of Arrangement, and Financing Assurances Review; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Central African Republic. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Fourth Review for the Central African Republic (CAR) under the three-year arrangement under the Poverty Reduction and Growth Facility (PRGF). Short-term fiscal policy of the CAR attempts to stabilize demand through government spending while preserving medium-term fiscal discipline. The revised program safeguards budgeted spending and incorporates new externally financed peace-process spending. Structural reforms are focused on areas critical to economic stability and the recovery of growth. IMF staff supports completion of the fourth review, augmentation of PRGF access, and program extension.